Weber B Fracture of the Lateral Malleolus with Concomitant Anterior Talofibular Ligament Injury following an Ankle Supination Injury - Mohammed Khalid Faqi; Abdulla AlJawder; Fahad Alkhalifa; Ali H. Almajed (Case Reports in Orthopedics)
The Lauge-Hansen (LH) classification attempts to predict patterns of ankle injuries based upon the preceding mechanism of injury. Although it is widely used in clinical practice, it has been criticized mainly due to numerous reports of cases conflicting the prediction system. Here, we report a case of a 32-year-old male who sustained a Weber B fracture of the lateral malleolus following a supination ankle injury, which was treated conservatively, following which the patient presented with ankle instability and was found to have concurrent anterior talofibular ligament tear. Critical review of the LH classification along with its shortcomings is discussed.